Synthesis of modified NaX catalyst and application of modified NaX catalyst in side chain alkylation of toluene and methanol

Through the synthesis and application of modified NaX catalysts, the problem of difficult to take into account the activity and stability of alkali-supported X-type zeolite catalysts is solved, which extends the service life of the catalyst and increases the methanol conversion rate and the total yield of styrene.

CN119160912APending Publication Date: 2024-12-20TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310948080.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The activity and stability of the alkali-supported X-type zeolite catalysts are difficult to take into account in the toluene methanol side chain alkylation reaction, resulting in a short service life of the catalyst and affecting industrial production.

Method used

The synthesis method of modified NaX catalysts is adopted, including calcining at high pH, ​​synthesis of boron and phosphorus-containing NaX catalysts in situ, and the catalyst is prepared by hydrothermal and calcining steps for the toluene methanol side chain alkylation reaction.

Benefits of technology

The catalyst is achieved while maintaining activity and stability, extending the catalyst's service time and life, and improving the methanol conversion rate and the total yield of styrene.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119160912A_ABST
    Figure CN119160912A_ABST
Patent Text Reader

Abstract

The invention discloses synthesis of a modified NaX catalyst and application of the modified NaX catalyst in side chain alkylation of toluene and methanol, three types of catalysts are prepared by adopting an in-situ synthesis method, the first type of catalyst is roasted at high pH to prepare the NaX catalyst, the second type of catalyst is subjected to in-situ synthesis of a boron-containing NaX catalyst, and the third type of catalyst is subjected to in-situ synthesis of a phosphorus-containing NaX catalyst. The three kinds of catalysts are applied to the toluene and methanol side chain alkylation reaction process, the catalysts can keep high activity and stability at the same time, the service time of the catalysts is prolonged, and the service life of the catalysts is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, in particular to the synthesis of a modified NaX catalyst and application thereof in the side chain alkylation of toluene and methanol. Background Art

[0002] Styrene is an important chemical raw material, widely used in the production of polystyrene, acrylonitrile-butadiene-styrene (ABS) resin, styrene-butadiene (SB) copolymer latex and unsaturated polyester resin. At present, the traditional production process of styrene is mainly ethylbenzene dehydrogenation, which accounts for about 80% of the total production capacity, but this technology has the disadvantages of low raw material conversion rate, high reaction temperature and complex process. The process route of producing styrene by toluene methanol side chain alkylation reaction has the advantages of short process, low energy consumption and few side reactions, which can well make up for the shortcomings of ethylbenzene dehydrogenation.

[0003] The side chain alkylation of toluene and methanol is a reaction catalyzed by weak acid and medium-strong alkaline sites. Alkaline-loaded X-type zeolite has become a hot topic of research because of its adjustable acidity and alkalinity and pore structure, which is more suitable for the side chain alkylation of toluene and methanol. However, loading more and stronger alkaline substances to increase the alkalinity of the catalyst will seriously reduce the structural stability of the catalyst, thereby reducing the stability of the catalyst. Therefore, it is difficult to balance the activity and stability of the alkaline-loaded X-type zeolite catalyst, which brings huge challenges to the industrialization of the process of preparing styrene by the side chain alkylation of toluene and methanol. Summary of the invention

[0004] The purpose of the present invention is to provide the synthesis of a modified NaX catalyst and its application in the side chain alkylation of toluene and methanol, so as to solve the problem that it is difficult to balance the activity and stability of the alkaline supported X-type zeolite catalyst used in the above-mentioned toluene and methanol side chain alkylation reaction.

[0005] To achieve the above object, the first aspect of the present invention provides a method for synthesizing a modified NaX catalyst, comprising the following steps:

[0006] (1) adding a sodium silicate solution into a sodium aluminate solution to form a mixed solution, stirring the mixed solution until it becomes a gel and then allowing it to stand;

[0007] (2) The mixed solution is placed in a hydrothermal reactor for hydrothermal reaction, then cooled to room temperature, dried, and calcined to obtain the catalyst NaX H .

[0008] Preferably, the silicon-to-aluminum ratio of sodium silicate to sodium aluminate is 0.5-2.

[0009] Preferably, the stirring temperature is 30°C and the stirring time is 8 hours; the hydrothermal temperature is 100°C and the hydrothermal time is 6 hours; the drying temperature is 80°C and the drying time is 12 hours; the roasting temperature is 500°C and the roasting time is 6 hours.

[0010] Preferably, the crystals are washed with deionized water to different pH values ​​before drying, the pH values ​​are 9, 11, and 13, respectively, and the prepared catalysts are NaX9, NaX 11 、NaX 13 .

[0011] Preferably, sodium borate solution is added to the mixed solution in step (1) to prepare a catalyst of B n -NaX H , n is the boron / silicon molar ratio.

[0012] Preferably, n=0.005, 0.01, 0.02, 0.03 or 0.05.

[0013] Preferably, sodium phosphate solution is added to the mixed solution in step (1), and the prepared catalyst is P i -NaX H , i is the phosphorus / silicon molar ratio.

[0014] Preferably, i=0.03, 0.05, 0.07 and 0.09.

[0015] A second aspect of the present invention provides a modified NaX catalyst, which is prepared by the synthesis method according to any one of claims 1 to 7.

[0016] A third aspect of the present invention provides an application of a modified NaX catalyst, wherein the catalyst is applied to a toluene methanol side chain alkylation reaction process.

[0017] Therefore, the present invention adopts the synthesis of the modified NaX catalyst and the application thereof in the side chain alkylation of toluene and methanol, and adopts an in-situ synthesis method to prepare three types of catalysts, wherein the first type is a NaX catalyst prepared by calcination at a high pH, ​​the second type is an in-situ synthesized boron-containing NaX catalyst, and the third type is an in-situ synthesized phosphorus-containing NaX catalyst. The three types of catalysts are applied to the side chain alkylation reaction process of toluene and methanol, and the catalysts can maintain activity and stability at the same time, thereby increasing the use time of the catalyst and prolonging the service life of the catalyst.

[0018] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 is a stability test diagram of the NaX9 catalyst of Example 1;

[0020] Figure 2 It is NaX of Example 1 11 Catalyst stability test chart;

[0021] Figure 3 It is NaX of Example 1 13 Catalyst stability test chart;

[0022] Figure 4 It is NaX of Example 1 H Catalyst stability test chart;

[0023] Figure 5 B of Example 2 0.005 -NaX H Catalyst stability test chart;

[0024] Figure 6 B of Example 2 0.01 -NaX H Catalyst stability test chart;

[0025] Figure 7 B of Example 2 0.02 -NaX H Catalyst stability test chart;

[0026] Figure 8 B of Example 2 0.03 -NaX H Catalyst stability test chart;

[0027] Fig. 9 B of Example 2 0.05 -NaX H Catalyst stability test chart;

[0028] Fig.10 is P of Example 3 0.03 -NaX H Catalyst stability test chart;

[0029] Fig.11 is P of Example 3 0.05 -NaX H Catalyst stability test chart;

[0030] Fig.12 is P of Example 3 0.07 -NaX H Catalyst stability test chart;

[0031] Fig.13 is P of Example 3 0.09 -NaX H Catalyst stability test chart;

[0032] Fig.14 This is a stability test chart of the Cat-5 catalyst of Comparative Example 1. DETAILED DESCRIPTION

[0033] The present invention will be further described below. It should be noted that this embodiment is based on the technical solution and provides a detailed implementation method and a specific operation process, but the present invention is not limited to this embodiment.

[0034] Example 1

[0035] The synthesis process of the first type of NaX catalyst is:

[0036] The prepared sodium silicate solution was slowly and uniformly added to the stirred sodium aluminate solution through a peristaltic pump, wherein the ratio of silicon to aluminum in sodium silicate and sodium aluminate was 1:1, and the mixture was vigorously stirred at 30°C for 8 hours, and then allowed to stand for 12 hours after the mixture gelled. The mixture was then placed in a stainless steel hydrothermal kettle lined with polytetrafluoroethylene, and after being hydrothermal at 100°C for 6 hours, it was cooled to room temperature, and the crystals were washed with deionized water to different pH values. The catalyst obtained after drying in an oven at 80°C for 12 hours and calcining in a muffle furnace at 500°C for 6 hours was named NaX m (m=9, 11, 13, H), m represents the pH value of different water washing degrees, and H represents that the crystals are not washed with water.

[0037] Example 2

[0038] The synthesis process of the second type of NaX catalyst is:

[0039] The prepared sodium silicate solution and sodium borate solutions of different concentrations were slowly and uniformly added to the stirred sodium aluminate solution through two peristaltic pumps. The subsequent preparation method was the same as that in Example 1. This series of catalysts was named B n -NaX H (n=0.005, 0.01, 0.02, 0.03 and 0.05), n represents the B / Si ratio, and H represents that the crystals are not washed with water.

[0040] Example 3

[0041] The synthesis process of the third type of NaX catalyst is as follows: the prepared sodium silicate solution and sodium phosphate solutions of different concentrations are slowly and uniformly added to the stirred sodium aluminate solution through two peristaltic pumps. The subsequent preparation method is the same as that in Example 1. This series of catalysts is named P i -NaX H (i=0.03, 0.05, 0.07 and 0.09), wherein i represents the P / Si ratio and H represents that the crystals are not washed with water.

[0042] Comparative Example 1

[0043] The preparation process of NaX zeolite powder is as follows:

[0044] The prepared sodium silicate solution was slowly and uniformly added to the stirred sodium aluminate solution through a peristaltic pump, and vigorously stirred for 8 hours at 30°C. After the mixture was gelled, it was allowed to stand for 12 hours. The mixture was then placed in a stainless steel hydrothermal kettle lined with polytetrafluoroethylene, and after being hydrothermalized at 100°C for 6 hours, it was cooled to room temperature, and the crystals were washed with deionized water until neutral. The catalyst obtained after drying in an oven at 80°C for 12 hours and calcining in a muffle furnace at 500°C for 6 hours was named NaX.

[0045] The catalyst was prepared by a solid-liquid continuous mixing method, and the specific steps are as follows: 0.15g, 0.25g, 0.35g, and 0.45g of KOH were dissolved in 50mL of distilled water respectively for standby use. 5g of NaX zeolite powder was added to 100mL of distilled water while stirring at 80°C, and the above four concentrations of KOH solution were added dropwise with a peristaltic pump. Based on the amount of NaX, the amount of potassium hydroxide added was 3wt.%, 5wt.%, 7wt.%, and 9wt.% of NaX respectively. After the addition was completed, the solution was stirred at 80°C for 1.5h and then cooled at room temperature. The cooled solution was dried in an oven at 80°C for 12h to evaporate the excess aqueous solution. The obtained solid was placed in a muffle furnace, heated to 500°C at a rate of 3°C / min and calcined for 3h. The obtained catalyst was named Cat-xK (x is mKOH / mNaX, 3wt.%, 5wt.%, 7wt.%, 9wt.%, respectively)

[0046] Test example

[0047] First, the catalysts prepared in Examples 1-3 and Comparative Example 1 were ground into fine powders, tableted and granulated, and 1.2 g of catalyst particles of 40-60 mesh were collected for catalytic evaluation in a fixed bed reactor. At 425°C, a mixed solution of toluene and methanol (molar ratio of 5) was continuously injected into a fixed bed reactor at a rate of 0.8 mL / h using a microinjection pump to carry out a side chain alkylation reaction, and then the reaction products were detected by gas chromatography, and the methanol conversion rate, product selectivity and side chain alkylation yield were calculated to investigate the catalyst stability. Tables 1-4 are activity data tables of the catalysts.

[0048] The catalyst activity and selectivity were calculated according to the following formula.

[0049]

[0050]

[0051]

[0052] Among them, n Mfeed 、n MexitIt represents the amount of methanol imported and exported substances, i represents each product: EB-ethylbenzene, ST-styrene, CH4-methane, XY-xylene, HCHO-formaldehyde.

[0053] Table 1 NaX of Example 1 m Catalytic activity data of catalysts

[0054]

[0055] Note: C M is the conversion rate of methanol, S EB is the product selectivity of ethylbenzene; S STY is the selectivity of styrene; S CH4 is the selectivity for methane; S XY is xylene; S HCHO is the selectivity of formaldehyde, Y EB is the yield of ethylbenzene; Y STY is the yield of styrene; Y (EB+STY) It is the sum of the yields of ethylbenzene and styrene.

[0056] From Table 1, it can be seen that the product selectivity is higher when the crystals are not washed with water. Figure 1-4 It can be seen that when the catalysts prepared in Example 1 are used to carry out the toluene methanol side chain alkylation reaction, as the catalyst usage time increases, the methanol conversion rate and the total yield of ethylbenzene and styrene do not change much, and the catalyst stability is relatively high.

[0057] Table 2 B of Example 2 n -NaX H Catalytic activity data of catalysts

[0058]

[0059] It can be seen from Table 2 that the unwashed catalyst NaX H After doping with boron, the total yield of ethylbenzene and styrene was further improved. Figure 5-9 It can be seen that each B n -NaX H During the 10-day use of the catalyst, the total yields of ethylbenzene and styrene changed little, and the methanol conversion rate also changed little, indicating that the boron-doped NaX H The catalyst has high stability. At the same time, the methanol conversion rate is also around 90%, indicating that boron-doped NaX H The activity of the catalyst is also high.

[0060] Table 3 P of Example 3 i -NaX H Catalytic activity data of catalysts

[0061]

[0062] It can be seen from Table 3 that the unwashed catalyst NaX H After doping with phosphorus, compared with NaX H The total yield of ethylbenzene and styrene was further improved by Figure 10-13 It can be seen that each P i -NaX H During the 10-day use of the catalyst, the total yield of ethylbenzene and styrene changed little, and the conversion rate of methanol also changed little, indicating that the phosphorus-doped NaX H The catalyst has high stability. At the same time, the methanol conversion rate is also around 90%, indicating that phosphorus-doped NaX H The activity of the catalyst is also high.

[0063] Table 4 Catalytic activity data of Cat-xK catalyst of Comparative Example 1

[0064]

[0065] It can be seen from Table 4 that when the amount of potassium hydroxide added to the Cat-xK catalyst is 0, most of the methanol is converted into xylene, and is not converted into styrene and ethylbenzene. The selectivity of styrene and ethylbenzene is low. When the amount of potassium hydroxide added to the Cat-xK catalyst is 3, 5, 7, and 9, the conversion rate of methanol is high, above 98%, and the total yield of ethylbenzene and styrene reaches 75%, with the highest being 97.82%, indicating that the activity of the catalyst is very high. However, Fig.14 It can be seen that after 7 days of continuous use of the Cat-xK catalyst, the selectivity of styrene and the total yield of ethylbenzene and styrene dropped sharply, indicating that the Cat-xK catalyst cannot be used for a long time and has low stability. This requires frequent replacement of the catalyst in the industrial preparation of styrene, which is not conducive to the continuous production of the product.

[0066] Therefore, the present invention adopts the synthesis of the modified NaX catalyst of the above structure and the application thereof in the side chain alkylation of toluene and methanol, and adopts the in-situ synthesis method to prepare three types of catalysts, wherein the first type of NaX catalyst is prepared by calcination at high pH, ​​the second type of boron-containing NaX catalyst is synthesized in-situ, and the third type of phosphorus-containing NaX catalyst is synthesized in-situ, and the three types of catalysts are applied to the side chain alkylation reaction process of toluene and methanol, and the catalyst can maintain activity and stability at the same time, thereby increasing the use time of the catalyst and prolonging the service life of the catalyst.

[0067] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for synthesizing a modified NaX catalyst, characterized in that: The following steps are involved: (1) adding a sodium silicate solution into a sodium aluminate solution to form a mixed solution, stirring the mixed solution until it becomes a gel and then allowing it to stand; (2) The mixed solution is placed in a hydrothermal reactor for hydrothermal reaction, then cooled to room temperature, dried, and calcined to obtain the catalyst NaX H .

2. The method for synthesizing the modified NaX catalyst according to claim 1, characterized in that: The silicon-aluminum ratio in sodium silicate and sodium aluminate is 0.5-2.

3. The method for synthesizing the modified NaX catalyst according to claim 2, characterized in that: The stirring temperature is 30°C and the stirring time is 8 hours; the hydrothermal temperature is 100°C and the hydrothermal time is 6 hours; the drying temperature is 80°C and the drying time is 12 hours; the calcination temperature is 500°C and the calcination time is 6 hours.

4. The method for synthesizing the modified NaX catalyst according to claim 3, characterized in that: Before drying, the crystals were washed with deionized water to different pH values, namely 9, 11, and 13. The prepared catalysts were NaX9, NaX 11 、NaX 13 .

5. The method for synthesizing the modified NaX catalyst according to claim 3, characterized in that: Sodium borate solution is also added to the mixed solution in step (1) to prepare a catalyst B n -NaX H , n is the boron / silicon molar ratio.

6. The method for synthesizing the modified NaX catalyst according to claim 5, characterized in that: n=0.005, 0.01, 0.02, 0.03 or 0.

05.

7. The method for synthesizing the modified NaX catalyst according to claim 3, characterized in that: Sodium phosphate solution is also added to the mixed solution in step (1) to prepare a catalyst of P i -NaX H , i is the phosphorus / silicon molar ratio.

8. The method for synthesizing the modified NaX catalyst according to claim 7, characterized in that: i=0.03, 0.05, 0.07 and 0.

09.

9. A modified NaX catalyst, characterized in that: The catalyst is prepared by the synthesis method according to any one of claims 1 to 8.

10. The use of a modified NaX catalyst according to claim 9, characterized in that: The catalyst is applied in the process of toluene methanol side chain alkylation reaction.

Citation Information

Patent Citations

  • Method for preparing styrene catalyst through toluene-methanol side chain alkylation

    CN101623650A

  • Method for preparing low-silicon NaX zeolite by applying activated silicon source

    CN102417190A

  • Primary crystallization hydrothermal preparation method of A-type and X-type molecular sieves containing pure Na ions

    CN102838127A

  • Catalyst for side chain alkylation reaction of toluene and methanol and application thereof

    CN106622338A

  • Preparation method and application of two-stage catalyst

    CN109395767A